Perancangan Panel Surya di Wilayah Kavling Rawa Bunga, Tangerang Selatan demi Penghematan Energi Masyarakat - M. Dibyo Setiawan; Fathan Mubina Dewadi (Journal of Entrepreneurship and Community Innovations, 2022)
Since youth are not merely social statuses that are easily ordered or treated with disdain, but also need to be appreciated by providing proper chances, the role of youth in starting a community service program does need to be followed up. Field research and literary analysis are the first steps in this innovation. The fact that doing simulation activities or innovations necessitates so many references is, of course, why a literature study is necessary. To ensure that the work done does not cease, this activity's last stage involves drawing conclusions till it becomes a report and publishing it. The Graha Raya's solar panel design is particularly adaptable because it simply uses the edge area as a solar panel roof. If there are people who want to engage in fishing activities and if they want to innovate more, this solar panel roof will be able to protect them from the heat.